Guide to producing national health accounts with special applications for low-income and middle-income countries (WHO GenevaCH)
Provides the conceptual and practical information needed to set up and implement national health accounts (NHA) in a country. Reflects developments in international standards and best practice experience gained from real-world efforts to draw up relevant and useful health accounts.
Keywords: HEALTH EXPENDITURE